A mechanochemical route for the synthesis of VNbO5 and its structural re-investigation using structure solution from powder diffraction data. Issue 29 (19th June 2019) - Valentoni, Antonio; Barra, Paolo; Senes, Nina; Mulas, Gabriele; Pistidda, Claudio; Bednarcik, Jozef; Torre, Francesco; Garroni, Sebastiano; Enzo, Stefano
Abstract : VNbO5 with a revised space group P 212121 versus Pnma has been successfully synthesized by a solvent-free mechanochemical route. Abstract : A new and solvent-free synthesis route has been adopted and optimized to prepare crystalline VNbO5 from the mechanochemical reaction between Nb2 O5 and V2 O5 as starting reagents. The substantially amorphous mixture of equimolar pentoxide V and Nb metals observed after extended mechanical treatment transforms into a crystalline powder following calcination under mild conditions at 710 K. The structure solution of the X-ray diffraction pattern using a global optimization approach, combined with Rietveld refinement, points to a space group P 21 21 21 (no. 19) different from Pnma (no. 62) previously proposed in the literature assuming it to be isostructural to VTaO5 . The new space group helps to describe weak peaks that remained previously unaccounted for and allows more reliable determination of atomic fractional coordinates and interatomic distance distribution. The as-prepared VNbO5 has been tested as a dopant (5 wt%) for the purpose of solid state hydrogen storage, decreasing significantly the release of hydrogen of MgH2 /Mg (620 K) and further enhancing the hydrogen sorption kinetic properties.